Efficiency comparison of a dc-dc interleaved converter based on SiC-MOSFET and Si-IGBT devices for EV chargers - Loncarski, Jelena (2020)
The charging process is one of the main factors for the widespread dissemination of electric mobility, therefore, the use of optimized power electronics converters is of utmost importance. In addition to innovative topologies, the use of emerging technologies of semiconductors is also crucial. In this context, using a three-phase interleaved dc-dc topology, a comparison between the use of SiC-MOSFET and Si-IGBT is presented in this paper, mainly in terms of operating efficiency. Two cases have been presented: 1) with the same inductor, where only power device losses have been considered; 2) with the same inductor current ripple, where different inductors have been considered and the analysis included also the inductor design and losses. The simulations were carried out in LTspice simulation tool on realistic dynamic models of power switch modules obtained from the manufacturer’s experimental tests. The results validate the use of SiC-MOSFET for the three-phase interleaved dc-dc topology showing lower losses for both the power devices and inductor and, most important, prove the advantages of its use in terms of efficiency for a wide range of operating powers.